A method for constructing uniform potential - Struzhanov, Valery Vladimirovich; Prosviryakov, Evgeny Yur'evich; Burmasheva, Natalia Vladimirovna (Computational Continuum Mechanics, 2009)
The uniform potential establishing a link between stresses and strains at all stages of deformation, including strain softening, is considered. A method for constructing this potential is developed. The method is based on the similarity of potential level lines in non-elastic and elastic fields. The validity of the method is verified by carrying out the tension-torsion, biaxial and triaxial deformation tests of material elements. Some illustrative examples are given.
Keywords: deformation theory; uniform potential; tension-torsion tests; biaxial deformation; triaxial deformation; level line